INTEGRATED WEED MANAGEMENT IN PIGEONPEA ( GEMENT IN PIGEONPEA (CAJANUS CAJAN L.) UNDER RAINFED CONDITIONS OF KARNATAKA - S. RATHOD, PANDIT; AND D. H. PATIL, B. M. DODAMANI (The Bioscan, 2016)
A field investigation was carried out during rainy seasons of 2010, 2011 and 2012 at Agricultural Research Station, Gulbarga (Karnataka) to evaluate the effect of pre and post emergent herbicides on weeds and productivity of pigeonpea. The pooled data of three years indicated that, pre emergence application of pendimethalin @ 0.75 kg a.i ha-1 – one hand weeding at 50 DAS recorded significantly higher weed control efficiency (97.4%) similar to that of weed free plot (97.4%) and was on par with hand weeding twice at 25 and 50 DAS (94.2%) at 70 DAS. Application of imazethapyr @ 75 g a.i. ha-1 at 20 DAS - paraquat @ 0.40 kg a.i. ha-1 at 6 weeks after sowing recorded significantly higher seed yield (1475 kg ha-1), more number of pods per plant (165.7), pod weight (68.39 g plant-1) and 100 seed weight (9.82 g) as compared to other treatments. Significantly lower seed yield (971 kg ha1 ) and yield parameters were recorded in weedy check treatment because of higher weed incidence and their competition throughout the growth period of pigeonpea.It can be concluded that, imazethapyr @ 75 g a.i. ha-1 at 20 DAS - paraquat @ 0.40 kg a.i. ha-1 at 6 WAS can be effectively used for controlling weeds and in obtaining optimum seed yield of pigeonpea.